Association Between Metabolic Syndrome and Immunohistochemical Profile at Breast Cancer Diagnosis in Postmenopausal Women - Motoki, Andre H. [UNESP]; Buttros, Daniel A.B. [UNESP]; Gaspar, Ana Luisa [UNESP]; Almeida-Filho, Benedito S. [UNESP]; Carvalho-Pessoa, Eduardo [UNESP]; Vespoli, Heloisa D.L [UNESP]; Nahas-Neto, Jorge [UNESP]; Nahas, Eliana A.P. [UNESP] (Elsevier, 2022)
Background: The aim of this study was to evaluate the association between metabolic syndrome (MetS) and the immunohistochemical profile of breast cancer (BC) in postmenopausal women. Methods: This cross-sectional cohort study included 189 women, aged 45 to 75years and amenorrhea >12 months, with newly diagnosed BC and no previous cancer treatment. Clinical, anthropometric and biochemical data were collected, as well as data on BC hormone status (estrogen receptor, ER; progesterone receptor, PR; human epidermal growth factor receptor-2, HER-2), and epithelial proliferative activity (Ki-67). Tumors were divided into 5 subtypes:luminal A, luminal B HER-2 negative, luminal B HER-2 positive, non-luminal HER-2, and triple negative. Women with three or more of the following criteria were diagnosed with MetS: waist circumference ≥88cm; triglycerides ≥150mg/dL; HDL-cholesterol <50mg/dL; blood pressure ≥130/85mmHg; glucose ≥100mg/dL. Results: Sixty-three (33.3%) of the 189 patients had MetS at the time of diagnosis. Women with MetS had a higher frequency of tumors ≤ 2cm than women without MetS (49.2% vs. 31.8%) (P = .038). There were no differences in histological grade, staging, or axillary lymph node metastasis (P > .05). The proportion of PR-positive (P = .006), HER-2-negative (P = .034), and luminal B HER-2-negative (P = .038) tumors was higher among patients with MetS compared to women without MetS (79.4% vs. 61.8%, 89.9% vs. 78.6% and 44.5% vs. 27.8%, respectively). Multivariate analysis adjusted for age, time since menopause and BMI showed a higher risk for luminal B HER-2-negative tumors among women with MetS (OR 2.00, 95% CI 1.03-3.89), obese patients (OR 2.03, 95% CI 1.06-3.90), and women with abdominal obesity (OR 1.96, 95% CI 1.01-4.03). Conclusion: In postmenopausal women with newly diagnosed BC, the presence of MetS was associated with smaller tumor size, PR-positive and HER-2-negative status, and the luminal B tumor subtype.
Keywords: Breast cancer subtypes; Hormone receptor status; Menopause; Metabolic Health; Obesity